(untitled) (Acta Polytechnica CTU Proceedings, 2022)
The paper deals with the phenomenon of long-pitch corrugation in curves of the small radii and also the effects that accelerate or slow down its development. The paper presents data from sections of railway track measured for new rails, rails before and after grinding or replacement. The effect of train speeds running through the curves and the associated cant deficiency or excess were studied. The tendencies of long-pitch corrugation development are described, which can be used to estimate when maintenance action or rail replacement will be necessary.